1997
DOI: 10.1006/dbio.1997.8630
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mammary Gland Development and Function in Mice Lacking LAR Receptor-like Tyrosine Phosphatase Activity

Abstract: The LAR receptor-like protein tyrosine phosphatase is composed of two intracellular tyrosine phosphatase domains and a cell adhesion molecule-like extracellular region containing three immunoglubulin-like domains in combination with eight fibronectin type-III-like repeats. This architecture suggests that LAR may function in cellular signalling by the regulation of tyrosine phosphorylation through cell-cell or cell-matrix interactions. We used gene targeting in mouse embryonic stem cells to generate mice lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 52 publications
0
78
0
Order By: Relevance
“…Independent laboratories reported that Stat5a (Liu et al, 1996;Teglund et al, 1998) and LAR (Schaapveld et al, 1997) are required for normal lobuloalveolar maturation and lactation at parturition. The possible coupling of ErbB2 signaling with the signaling pathways of Stat5a and LAR or both, deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Independent laboratories reported that Stat5a (Liu et al, 1996;Teglund et al, 1998) and LAR (Schaapveld et al, 1997) are required for normal lobuloalveolar maturation and lactation at parturition. The possible coupling of ErbB2 signaling with the signaling pathways of Stat5a and LAR or both, deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Normal mammary morphogenesis but impaired function is observed in the absence of the cytoplasmic phosphatase LAR (Schaapveld et al 1997). Although the molecular basis of this defect is unclear, it has been shown that LAR is found in focal adhesion sites.…”
Section: Signaling Within the Cellmentioning
confidence: 99%
“…Less clear are some of the signaling events leading to the functional differentiation of the epithelium. In particular, the roles which CSF-1 (Pollard and Hennighausen 1994) and LAR (Schaapveld et al 1997) play in the mammary gland need to be defined.…”
Section: Systemic Hormones and Inductive Epithelial-stromal Interactimentioning
confidence: 99%
See 1 more Smart Citation
“…The PTPs in this family exhibit extracellularly structural features characteristic of adhesion molecules and reveal a high degree of homology to each other suggesting that they may partially be redundant with respect to function. This assumption is supported by the ®nding that mice with an inactivated LAR gene are viable and have a more subtle phenotype in mammary gland development (Skarnes et al, 1995;Schaapveld et al, 1997b). On the other hand, the PTPs in this family exist in multiple isoforms arising by alternative splicing, suggesting possibly very speci®c functions in dierent cell types or developmental stages (Longo et al, 1993;Ogrady et al, 1994;Rotin et al, 1994;Zhang and Longo, 1995;Pulido et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%